Peran Tenaga Administrasi Sekolah Dalam Layanan Administrasi di SMP Cokroaminoto Tamalanrea Makassar - Srini Rianti; Andi Mappincara; Andi Wahed (Universitas Negeri Makassar, 2022)
Abstract. This study examines the role of TAS in administrative services at Cokroaminoto Tamalanrea Junior High School Makassar. This study aims to find out the role of administrative personnel in carrying out administrative services and to find out the supporting factors and obstacles to administrative services. The approach used is a qualitative type of descriptive research. Data collection techniques in the form of interviews, observations, and documentation. Data analysis techniques use miles and Huberman models. They are checking the validity of data using triangulation techniques. The results showed that TAS's role in administrative services known as the new school has carried out several tupoksinya including student administration affairs, staffing administration affairs, administrative affairs of the community and archives, curriculum administration affairs, special education service administration affairs. Not yet fully implemented as the guidance of the school administration / madrasah workforce. Supporting factors are work experience and abilities possessed and facilities and infrastructure facilities. Inhibiting factors are miscommunication between employees, administrative personnel do not know the existence of guidance from the ministry, there is no training training, there is no tendik supervision, administrative personnel play the role of new employees, not with the background of administrative graduates, some teachers concurrently become administrative personnel. Abstrak. Penelitian ini mengkaji tentang Peran TAS dalam Layanan Administrasi di SMP Cokroaminoto Tamalanrea Makassar. Tujuan dari penelitian ini adalah untuk mengetahui Peran Tenaga Administrasi dalam melaksanakan layanan administrasi dan untuk mengetahui faktor pendukung dan penghambat dalam layanan administrasi. Pendekatan yang digunakan adalah kualitatif jenis penelitian deskripsi. Teknik pengumpulan data berupa wawancara, observasi, dokumentasi. Teknik analisis data menggunakan model Miles dan Huberman. Pengecekan keabsahan data menggunakan teknik triangulasi. Hasil penelitian menunjukkan dalam melaksanakan peran TAS dalam layanan administrasi diketahui sebagai sekolah baru sudah menjalankan beberapa tupoksinya diantaranya urusan administrasi kesiswaan, urusan administrasi kepegawaian, urusan administrasi persuratan dan kearsipan, urusan administrasi kurikulum, urusan administrasi layanan khusus. Belum sepenuhnya dijalankan sebagaimana panduan kerja tenaga administrasi sekolah/madrasah. Faktor pendukung yaitu pengalaman kerja dan kemampuan yang dimiliki serta fasilitas sarana dan prasarana. Faktor penghambat yaitu mis communication antar pegawai, tenaga administrasi tidak mengetahui keberadaan panduan dari kementrian, tidak ada pelatihan diklat, tidak ada supervisi tendik, tenaga administrasi berperan pegawai baru, tidak berlatarbelakang lulusan administrasi, beberapa guru merangkap jadi tenaga administrasi.